Implementation of project-based learning model to improve students’ product creativity in natural sciences learning - Febrina Addaafi; Sri Utami (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2023)
Improving students’ creativity is very important in 21st-century education. One form of creativity is the ability to develop a product. Based on the observation, students already had the potential for creative thinking, but they had difficulties expressing these ideas in a product. This study was conducted to determine the improvement in students’ product creativity in Natural Science learning with the implementation of the Project-Based Learning (PjBL) model. The method used was classroom action research consisting of two cycles. Each cycle included three stages, namely planning, implementing, and reflecting. Data were collected through observation notes and documentation during the activities. The results of this study indicate that learning by implementing the Project-Based Learning (PjBL) model in the Natural Sciences subject can increase the creativity of students’ products. It is evidenced by an increase in student creativity by 24.45 based on the product assessment from cycle I which was 64.44 and cycle II was 88.89. In cycle I, improvements were still needed, but in cycle II students were more creative in preparing tools and materials, making products neater and paying attention to color matching, and generating relatively new and unique product ideas.Keywords: Project-based learning, product creativity, Natural Sciences, classroom action research